The contributions of teaching learning methodology preferences, motivation, commitment and participation to preparatory school science students' academic achievement: Bahir Dar city in focus - Amera Belayneh (College of education, Bahir Dar University, 2023)
The main purpose of this study is to examine the contributions of preparatory school science students' independent and group learning methodology preferences, motivation, commitment and participation to their academic achievement. The study also checked the differences in prevalence of the study variables in public and private school science students. Simple random sampling, stratified random sampling, and purposive sampling techniques were employed. Data were collected from 214 (121 male and 93 female) preparatory school science students through questionnaire. Eight participants were interviewed. One sample t-test, independent sample t-test and multiple regression analyses were the data analysis techniques. The study found that both public and private preparatory school science students' academic achievement, participation and group learning methodology preferences were above the expected average. However, students' independent learning preferences, motivation and commitment in learning were below the expected level. Around 38% of students' academic achievement was mainly attributed to the multiple contributions of motivation, commitment and independent learning methodology preferences. In comparison to public preparatory schools, private preparatory school science students were better in their academic achievement, independent learning methodology preferences, motivation and commitment, but they did not have significant differences in their participation and group learning methodology preferences. Based on the findings, the study suggested that preparatory school science teachers, students and the management (particularly in public schools) need to initiate the teaching learning processes towards strict, challenging and hardworking contexts. This may help students to develop the real senses of using proper learning methodologies, appropriate motivation, commitment and participation rather than unnecessarily inclining towards one learning methodology (e.g. group learning method) over the other (e.g. independent learning method) since both of them will have their own time and place.